(8c+d)(2c+3d)=

Simple and best practice solution for (8c+d)(2c+3d)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8c+d)(2c+3d)= equation:


Simplifying
(8c + d)(2c + 3d) = 0

Multiply (8c + d) * (2c + 3d)
(8c * (2c + 3d) + d(2c + 3d)) = 0
((2c * 8c + 3d * 8c) + d(2c + 3d)) = 0

Reorder the terms:
((24cd + 16c2) + d(2c + 3d)) = 0
((24cd + 16c2) + d(2c + 3d)) = 0
(24cd + 16c2 + (2c * d + 3d * d)) = 0
(24cd + 16c2 + (2cd + 3d2)) = 0

Reorder the terms:
(24cd + 2cd + 16c2 + 3d2) = 0

Combine like terms: 24cd + 2cd = 26cd
(26cd + 16c2 + 3d2) = 0

Solving
26cd + 16c2 + 3d2 = 0

Solving for variable 'c'.

Factor a trinomial.
(8c + d)(2c + 3d) = 0

Subproblem 1

Set the factor '(8c + d)' equal to zero and attempt to solve: Simplifying 8c + d = 0 Solving 8c + d = 0 Move all terms containing c to the left, all other terms to the right. Add '-1d' to each side of the equation. 8c + d + -1d = 0 + -1d Combine like terms: d + -1d = 0 8c + 0 = 0 + -1d 8c = 0 + -1d Remove the zero: 8c = -1d Divide each side by '8'. c = -0.125d Simplifying c = -0.125d

Subproblem 2

Set the factor '(2c + 3d)' equal to zero and attempt to solve: Simplifying 2c + 3d = 0 Solving 2c + 3d = 0 Move all terms containing c to the left, all other terms to the right. Add '-3d' to each side of the equation. 2c + 3d + -3d = 0 + -3d Combine like terms: 3d + -3d = 0 2c + 0 = 0 + -3d 2c = 0 + -3d Remove the zero: 2c = -3d Divide each side by '2'. c = -1.5d Simplifying c = -1.5d

Solution

c = {-0.125d, -1.5d}

See similar equations:

| 10y-5-5y=15 | | .25x+20=-30 | | y-1/5=5/7 | | 12=q+2 | | 4(x+6)+18x=134 | | 6+[8x-3]=12 | | 1+p=-5-2p | | 8x^3-16x^2+6x=0 | | -x-1=-4x+5 | | 4/9=24/m | | 5u-w=u-6w | | 37x+5=6(6x+7) | | 9x-4(x-6)=3(x-2)+9 | | 2(1-0+4)= | | -91y-87=y-78 | | 1=137-4z+2z | | 350=-2x-15 | | (6y+6)-(5+5y)=7 | | x+(x*.3)=20 | | y/20 | | 58=4x+x+8 | | 67y-14=y-99 | | n+8=-2n-1 | | -3+10=2x+9 | | 2(1-1+4)= | | 9rd^4-9rk^2= | | (3+x)x=26 | | Z+8=20 | | 7r^2-7r+6=6 | | 50p-2=6p-9 | | d/34 | | (5v+9)(7-v)=0 |

Equations solver categories